Sex Differences in Cue Competition Effects With a Conditioned Taste Aversion Preparation - Angulo, Rocio; Bustamante, Javier; Estades, Vania; Ramírez, Valeska; Jorquera, Belén (Frontiers in Behavioral Neuroscience, 2020)
This study aimed to test whether male and female rats might show differences in cue competition effects in a conditioned taste aversion preparation. Experiment 1 tested for sex differences in overshadowing, finding the usual effect of overshadowing in males but not in females. Experiment 2 examined for sex differences in blocking. Similarly, the blocking effect appeared in males but not in females. The present findings thus support the hypothesis that sexual dimorphism might be expressed in classical conditioning, or at least, in cue competition effects such as overshadowing and blocking with taste aversion preparations.